Collateral scarcity and market functioning: Insights from the eurosystem securities lending facilities - Stefan Greppmair; Stephan Jank (Deutsche Bundesbank, 2023)
We utilize the Eurosystem securities lending facilities as a laboratory to investigate the impact of collateral scarcity on market functioning. The reduction of securities lending fees, implemented in November 2020, provides a natural experiment for our analyses. This policy change results in a surge in the utilization of securities lending facilities, particularly for bonds with limited supply elasticity in the repo market. We find no evidence of substitution effects; instead, the overall activity in the repo market expands through the collateral multiplier. The improved pricing conditions alleviate collateral scarcity and enhance market quality in both the repo and cash markets.
Keywords: G10; G21; E50; E58; 330; safe assets; collateral scarcity; monetary policy; quantitative easing; securities lending facilities; repo; market functioning